Integration of Character Values Based on Thomas Lickona's Theory in the Berau Folktale Batu Bual as an Innovation for Modern Learning - Tita Sabrina Oktavianty; Nia Novita Putri (JENTERA: Jurnal Kajian Sastra, 2026)
This study aims to analyze the character education values in the Batu Bual folktale from Berau Regency based on Thomas Lickona's theory of character education. The research employs a descriptive qualitative method with content analysis techniques. The primary data source is the book Cerita Rakyat Paser dan Berau (Folktales of Paser and Berau), while the research data consist of textual excerpts containing character education values. Data were collected through library research involving a comprehensive reading and examination of the folktale text. Data analysis followed Miles and Huberman's interactive model, comprising data reduction, data display, and conclusion drawing. The findings reveal that the Batu Bual folktale contains character education values, including honesty, responsibility, patriotism, healthy competition, harmony, and cooperation. These values are reflected through the characters' attitudes and actions, which embody the aspects of moral knowing, moral feeling, and moral action. Accordingly, the Batu Bual folktale can be utilized as a local wisdom-based medium for character education for younger generations. Abstrak Penelitian ini bertujuan untuk menganalisis nilai-nilai pendidikan karakter dalam cerita rakyat Batu Bual dari Kabupaten Berau berdasarkan teori pendidikan karakter Thomas Lickona. Penelitian menggunakan metode deskriptif kualitatif dengan teknik analisis isi. Sumber data utama berasal dari buku Cerita Rakyat Paser dan Berau, sedangkan data penelitian berupa kutipan teks yang mengandung nilai pendidikan karakter. Teknik pengumpulan data dilakukan melalui studi pustaka dengan membaca dan menelaah teks cerita rakyat secara menyeluruh. Analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa cerita rakyat Batu Bual mengandung nilai pendidikan karakter berupa kejujuran, tanggung jawab, patriotisme, persaingan yang sehat, harmoni, dan kerja sama. Nilai-nilai tersebut tercermin melalui tindakan dan sikap tokoh yang menunjukkan aspek moral knowing, moral feeling, dan moral action. Dengan demikian, cerita rakyat Batu Bual dapat dimanfaatkan sebagai media pendidikan karakter berbasis kearifan lokal bagi generasi muda.